The Role of Virtual Reality in Treating Phobias: a Systematic Review - Soliev Mukhammadkhon Bobirshoevich; Igamova Saodat Suratovna; Saidafzal Shukurov Ma’murovich; Bobirjon Bakhtiyorov Bahtiyorovich; Fayzullokhon Mavlyudov Sadulloxonovich (American Journal of Biomedicine and Pharmacy, 2025)
This systematic review evaluates the use of Virtual Reality (VR) technology in the treatment of phobias and Post-Traumatic Stress Disorder (PTSD), particularly in exposure therapy. VR-based treatments have been presented as new techniques that could provide immersive and controlled environmentsfor psychological disorder interventions. This manuscript pools data from various research studies assessing the efficacy, scope, and limitations of using VR therapy in comparison to traditional therapeutic strategies. Evidence now suggests that exposure therapy using VR has several advantages, including the creation of simulated environments difficult or impossible to reproduce in real life, the provision of gradual and safe exposure of patients to phobic stimuli, and increased user engagement. Moreover, VR therapy has shown promising results in reducing symptoms of PTSD by reprocessing traumatic memories in controlled environments. Besides, the integration of Human-Computer Interaction (HCI) aspects into virtual reality systems increases the personalization of treatment, and it can be easily tailored for patients presenting various types of phobias, including acrophobia, social anxiety disorder, and glossophobia. However, barriers such as financial constraints, cybersickness, and variability in therapeutic outcomes across different disorders slow down the development of VR therapy. This paper presents a wide-coverage, in-depth review of 10 case studiesinvolving participants with specific phobias and PTSD to emphasize the flexibility of VR in psychological interventions. These findings provide proofthat VR can revolutionize exposure therapy and lead to more effective, scalable, and accessible mental health treatments